A poliomyelitis survey the simple way: the Tanzanian experience. Issue 6494 (24th August 1985) - Cross, A B; Webber, R H
Abstract : A simple cost effective survey to assess the need for a rehabilitation service for individuals disabled by poliomyelitis was carried out making the maximum use of the existing government administration. The field team consisted solely of a medical officer and a health officer. The prevalence rate for paralytic poliomyelitis in the Mbeya region of Tanzania was 2.95/1000 persons. The rate for children under 10 years was 1.15/1000, suggesting that the expanded immunisation programme started in 1977 was being successful. With approximately 4000 cases of paralytic poliomyelitis in the Mbeya region a rehabilitation service would seem to be justified. If poliomyelitis surveys are required for rehabilitation purposes they must include all age groups. In this survey, had only school children been considered, as recommended by the World Health Organisation, two thirds of the cases would have been excluded, thereby hardly justifying a rehabilitation service.